Effects of the Picture and Picture Learning Model on Students’ Conceptual Understanding and Mathematics Achievement - Dwiani Kartika; Samnur Saputra; Sindi Amelia; Dadang Juandi; Adilah Abdul Ghopur (Department of Mathematics Education Program IPI Garut, 2025)
Penelitian ini bertujuan untuk mengkaji pengaruh model pembelajaran Picture and Picture terhadap pemahaman konseptual dan prestasi belajar matematika peserta didik. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen post-test only control group. Subjek penelitian terdiri atas 58 peserta didik kelas VIII yang dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Data dikumpulkan melalui tes uraian untuk mengukur pemahaman konseptual dan prestasi belajar matematika. Data dianalisis menggunakan one-way Multivariate Analysis of Variance (MANOVA). Hasil penelitian menunjukkan adanya perbedaan multivariat yang signifikan antara kedua kelompok, dengan peserta didik pada kelompok eksperimen memperoleh skor pemahaman konseptual dan prestasi belajar matematika yang lebih tinggi dibandingkan kelompok kontrol. Temuan ini menunjukkan bahwa penggunaan gambar berurutan secara terstruktur dalam model pembelajaran Picture and Picture mampu meningkatkan pemahaman konseptual sekaligus mendukung peningkatan prestasi belajar matematika peserta didik pada jenjang Sekolah Menengah Pertama. This study aimed to examine the effect of the Picture and Picture learning model on students’ conceptual understanding and mathematics achievement. A quantitative approach was employed using a quasi-experimental post-test only control group design. The participants consisted of 58 eighth-grade students divided into an experimental group and a control group. Data were collected through open-ended test items designed to assess conceptual understanding and mathematics achievement. The data were analyzed using one-way Multivariate Analysis of Variance (MANOVA). The results revealed a significant multivariate difference between the two groups, with students in the experimental group achieving higher scores in both conceptual understanding and mathematics achievement than those in the control group. These findings indicate that the structured use of sequential images in the Picture and Picture learning model supports students in organizing mathematical ideas and contributes to improved mathematics achievement at the junior high school level.